2016
DOI: 10.1049/iet-syb.2015.0059
|View full text |Cite
|
Sign up to set email alerts
|

Extended particle swarm optimisation method for folding protein on triangular lattice

Abstract: In this study, the authors studied the protein structure prediction problem by the two-dimensional hydrophobic-polar model on triangular lattice. Particularly the non-compact conformation was modelled to fold the amino acid sequence into a relatively larger triangular lattice, which is more biologically realistic and significant than the compact conformation. Then protein structure prediction problem was abstracted to match amino acids to lattice points. Mathematically, the problem was formulated as an integer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Furthermore, we have selected the most used instances in the literature to conduct the forthcoming experiments. The used benchmark sequences are shown in Table 1, where the symbol Table 2 shows a comparison of the best results taken from the above-stated algorithms used to solve the PSP problem in the 2D triangular lattice model, namely HGA [22], TS [23], ERS-GA [24], HHGA [24], IMOG [26], EPSO [25], and our suggested approach GALSTS. For each instance given in Table 2, we observe that the best solutions obtained by GALSTS are better or equal than all the cited approaches bellow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we have selected the most used instances in the literature to conduct the forthcoming experiments. The used benchmark sequences are shown in Table 1, where the symbol Table 2 shows a comparison of the best results taken from the above-stated algorithms used to solve the PSP problem in the 2D triangular lattice model, namely HGA [22], TS [23], ERS-GA [24], HHGA [24], IMOG [26], EPSO [25], and our suggested approach GALSTS. For each instance given in Table 2, we observe that the best solutions obtained by GALSTS are better or equal than all the cited approaches bellow.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, two approaches have been proposed in [24], including the Elite-based Reproduction Strategy-Genetic Algorithm (ERS-GA), and a Hybridization of Hill-climbing and Genetic Algorithm (HHGA) that combine the ERS-GA with a hill-climbing algorithm. Recently, an Extended Particle Swarm Optimization method (EPSO) was applied to PSP in [25]. A new approach called IMOG was proposed in [26], which combines Ions Motion Optimization algorithm (IMO) with a Greedy algorithm, the authors showed that IMOG algorithm has good search ability and stability using benchmark data sets.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason many researchers have been attracted to study this problem by proposing many heuristic algorithms. In recent years, for 2D HP protein folding problem, many methods have been proposed, e.g., PSO (Particle Swarm Optimization) [ 2 ], ACO (Ant Colony Algorithm) [ 3 ], ABO (Artificial Bee Colony) [ 4 ] and SOM (Self-Organizing Mapping) [ 5 ] etc.…”
Section: Introductionmentioning
confidence: 99%